Checklist of Staphylinidae (Coleoptera) of El Salvador - Pablo-Cea, José D.; Asenjo, Angélico; Navarrete-Heredia, José L.; Newton, Alfred F. (Zootaxa, 2021)
This paper is primarily a compilation of published data on the staphylinid beetle species reported for El Salvador. It is based on taxonomic and ecological literature, with inclusion of some new records from different entomological collections. Thirty eight genera and 96 species are reported in the list, including a first country record: Eulissus chalybaeus. Country-level distribution outside of El Salvador, locality references and topographic zones are included for each species. In the list, three endemic species are recorded: Seeversiella badia, S. minima and Stenus salvadorensis. It is remarkable that 14 genera (37%) and 52 species (54%) have only been reported at a country level in the literature, without a specific locality of collection, indicating the need for local inventories of this coleopteran family in the salvadoran territory.